Ultra‐thin electromagnetic bandgap backed fractal geometry‐based antenna for 24 GHz ISM band WBAN. Issue 3 (27th January 2023) - Ali, Mubasher; Ullah, Irfan; Batchelor, John C.; Gomes, Nathan J.
Abstract: A compact, ultra‐thin electromagnetic bandgap (EBG) backed antenna is presented for the 24 GHz ISM band for WBAN applications. The proposed antenna has Koch fractal geometry‐based bow‐tie slots, designed with an overall dimension of 0.91 λ 0 ${λ }_{0}$ × 0.84 λ 0 ${λ }_{0}$ × 0.01 λ 0 ${λ }_{0}$ and backed by a 5 × 5 element 0.01 λ 0 ${λ }_{0}$ thick EBG structure; it is fabricated on a flexible Rogers 5880 substrate (thickness = 0.127 mm and dielectric constant ε r ${ε }_{r}$ = 2.2, tan δ = 0.0009). In comparison to the previously published K band prototype antennas, our presented fractal antenna has a more compact and ultra‐thin form factor. The low profile, via‐less EBG unit cell structure with dimensions of 0.254 λ 0 ${λ }_{0}$ × 0.254 λ 0 ${λ }_{0}$, possesses both Artificial Magnetic Conductor (AMC) and EBG characteristics. It is straightforward to fabricate at a millimeter‐scale. The performance parameters of the design are investigated in terms of on‐body reflection coefficient and free‐space radiation patterns with and without structural bending. The EBG structure enhances the antenna's front‐lobe gain by 2.3 dB, decreases back‐lobe radiation by 12.6 dB and decreases the specific absorption rate (SAR [1 g]) from >50.9 W/kg to <6.14 W/kg, significantly reducing the potential harm to the human body. Experimental investigations revealed high insensitivity of the proposed antenna to body proximity, and the performance is preserved with structural deformation. Abstract : An ultra‐thin, and compact electromagnetic bandgap (EBG)‐backed Koch fractal antenna structure is presented and its periodic structure shows both AMC and EBG characteristics in the 24 GHz ISM band. This structure is compact and electrically thinner than comparable structures of the K band in literature. Experimental investigations revealed high insensitivity of the proposed antenna to body proximity, and performance is preserved with structural deformation.